Analisis Fundamental Makro,Fundamental Mikro Terhadap Nilai Perusahaan Dengan Karakteristik Perusahaan,Kinerja Keuangan,Financial Laverage Variable Pada Perusahaan Manufaktur Tahun 2019-2023 - Cailah Nasywa A.; Hwianus Hwianus (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This research aims to analyze and test factors that have the potential to influence company value (Y) using quantitative methods with the Partial Least Square (PLS) approach. The data used comes from 10 manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. The variables in this research consist of attachment variables, namely company value (Y), and independent variables, such as Macro Fundamentals (Z1), Micro Fundamentals (Z2), Financial Performance (X1), Company Characteristics (X2), and Financial Leverage (X3 ). The analysis technique used is Partial Least Square (Smart PLS). The research results show that Financial Leverage has a positive but not significant influence on company value, while on financial performance it has a negative and not significant influence. Macro Fundamentals do not significantly affect Financial Leverage, but have an insignificant positive effect on company characteristics, financial performance and company value. Micro Fundamentals have a positive and significant effect on Financial Leverage, company characteristics and financial performance, but are not significant on company value. Company characteristics have a negative and significant effect on financial performance and company value. Financial performance has a positive but not significant effect on company value. This research contributes to the literature by providing empirical evidence regarding the factors that influence firm value in the Indonesian manufacturing sector. These findings can be used by investors, financial analysts, and other stakeholders to gain better understanding in making investment decisions.